Quantifying AEC professionals cross-work culture productivity: comparison between Malaysian and UK projects during industrialized building project - Abdul Ghafar, Maszura; Ibrahim, Rahinah (Emerald, 2023)
Purpose: This paper discussed quantifying architect, engineer and contractor (AEC) professionals' cross-work culture productivity by comparing between Malaysian and United Kingdom (UK) projects during industrialized building project delivery. This study addressed the second part of a mixed method research design study. Design/methodology/approach: This study hypothesized that with understanding of cultural work knowledge between professionals during design phase coupled with competent technological support, productivity can be improved. It utilized Cognitive Organizational Theory (COT) protocols to test conceptual models in SimVision®. Organizational structure, project intensity, and statistical validations parameters were performed to obtain the reliability and generalization of the result. Findings: This study found that with Building Information Modeling (BIM) technology intervention, the handling of exception, coordination and decision-making time could be improved, resulting in better project performances. The result also indicated that in choosing organizational fit, national culture factor needed to be considered; otherwise, organizational change would be unacceptable. By changing the operational process from intensive to reciprocal task intensity with BIM technology intervention, the effect on productivity would be similar to changing hierarchical organizational structure to flatter organizational structure. Research limitations/implications: Project discrepancies issues are limitedly discussed due to companies' confidentiality. The paper only focuses on understanding the effects of human factors during the integrated project delivery phase. Practical implications: The findings could support developing countries' professionals to collaborate effectively with developed countries' professionals. Originality/value: The development of the project's cultural knowledge experimentations will provide guidance to teams involved in international projects from developed and developing countries in pursuing joint ventures in project deliveries in either country successfully.